2021
DOI: 10.1210/clinem/dgab364
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Lipids During Pregnancy, Insulin-like Growth Factor-1, and Excess Fetal Growth

Abstract: Background Maternal lipids during pregnancy and placental growth factors are associated with excess foetal growth. However, how these factors interact to increase the risk of delivering large-for-gestational-age (LGA) neonates remains unclear. In this study, we investigated the relationship between maternal plasma triglyceride (TG) and free fatty acids (FAs) during pregnancy, cord blood insulin-like growth factors (IGF) and LGA. In a cell model, we studied the effect of different FAs on place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…The influence of TG during pregnancy has gained some attention, and we found a stable association between TG with birth weight and adverse birth outcomes in all of the BMI groups in the current study. Our study is in line with several previous studies that reported a positive association between maternal TG concentrations in early pregnancy and higher birth weight and LGA ( 36 38 ). In a study proposed by Wang et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The influence of TG during pregnancy has gained some attention, and we found a stable association between TG with birth weight and adverse birth outcomes in all of the BMI groups in the current study. Our study is in line with several previous studies that reported a positive association between maternal TG concentrations in early pregnancy and higher birth weight and LGA ( 36 38 ). In a study proposed by Wang et al.…”
Section: Discussionsupporting
confidence: 93%
“…The influence of TG during pregnancy has gained some attention, and we found a stable association between TG with birth weight and adverse birth outcomes in all of the BMI groups in the current study. Our study is in line with several previous studies that reported a positive association between maternal TG concentrations in early pregnancy and higher birth weight and LGA (36)(37)(38). In a study proposed by Wang et al in 2016, maternal TG concentrations in early pregnancy were divided into quartiles, and they did not observe any association between the highest quartile and an increased prevalence of LGA, whereas in the current study, the highest TG quartile showed a significantly higher risk of LGA (39).…”
Section: Discussionsupporting
confidence: 93%
“…A previous study had found increased ceramide in placenta from normal-weight fetuses compared to those with intra-uterine growth restriction (IUGR), consistent with our current findings in females [ 64 ]. Ceramides likely affect fetal growth by acting as signaling molecules, decreasing the expression of nutrient transporters [ 65 , 66 , 67 ], and regulating placental inflammation, insulin signaling, AKT activation, and amino acid transport [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Negative associations of birthweight centile with OA-TGs in female cases, meanwhile, might indicate reduced sequestration of OA into TG storage, making it more available for transfer to the fetus, especially since cord plasma OA has previously been linked with increased birthweight [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of growth signaling highlights the tight correlation between in utero environment and the epigenetic programming. Indeed, excessive fetal growth observed in LGA neonates results in part from gestational hyperglycemia, dyslipidemia, or over secretion of placental insulin-like growth factors [25][26][27]. Altogether, these results further illustrate how DNA methylation and chromatin accessibility are key co-epigenetics actors regulating TF activity.…”
Section: Discussionmentioning
confidence: 75%